PERSEPSI MAHASISWA PENDIDIKAN AGAMA ISLAM TERHADAP MODERASI BERAGAMA DI STAI DDI MAROS - Taqwim, Ahsan; Wahyuni, Wahyuni (IQRA : JURNAL PENDIDIKAN ISLAM, 2024)
This study aims to examine the perceptions of Islamic Education (PAI) students at STAI DDI Maros regarding religious moderation and the factors influencing it. The research method used is qualitative with an in-depth interview approach involving 5 students and 3 PAI lecturers, and the data were analyzed using thematic analysis. The results indicate that the majority of students have a basic understanding of religious moderation, which includes tolerance, openness, and mutual respect among religious groups. However, the level of understanding varies based on academic and non-academic experiences. Around 70% of students demonstrate a good understanding of religious moderation, 20% have a moderate understanding, and 10% still hold more normative views. Senior students (semester V and VII) show a deeper understanding compared to freshmen (semester I). The study also found that the main factors influencing students' perceptions of religious moderation are the academic environment (68%), non-academic activities (54%), and social media (48%). The implications of this study suggest that integrating religious moderation values into the Islamic Education curriculum and strengthening non-academic activities can deepen students' understanding of religious moderation and enhance their ability to become agents of change in society.